O Papel dos testemunhos dos Aikewara no Relatório Final da Comissão Estadual da Verdade e Memória do Pará - CARVALHO, Carla Jessica dos Santos (2024)
This work aims to understand oral sources and their role in truth commission investigations by analyzing the use of Aikewara testimonies in the final report of the State Truth Commission of Pará (CEV-PARÁ). As specific objectives, we sought to conceptualize testimonies based on definitions from oral sources and archives; understand the work of the National Truth Commission (CNV) and CEV-PARÁ within the scope of investigations into human rights violations during the Brazilian military dictatorship; and present the use of the Aikewara testimonies in the CEV-PARÁ investigations, starting from Chapter 8, in section II of the Final Report. This is exploratory research, with a qualitative and descriptive approach, which uses bibliographic, and documentary means, carrying out a bibliographic review and using the final reports and websites of the CNV and CEV-PARÁ. As a result, testimonies/testimonies are presented from the Aikewara indigenous peoples in the CEV-PARÁ final report, highlighting their importance for the recognition of human rights violations of traditional peoples during the military dictatorship in the state of Pará. Wait This research will contribute to new debates on the archives of the military dictatorship in the state of Pará and oral sources, with an emphasis on investigations into human rights violations committed against traditional peoples, in order to give them visibility and collaborate in forms of replacement and justice.